Bilateral De-Jure Exchange Rate Regimes and Foreign Direct Investment: A Gravity Analysis - Philipp Harms; Jakub Knaze (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper uses a newly constructed dataset on bilateral de-jure exchange rate regimes to estimate the effect of expected exchange rate volatility on foreign direct investment (FDI). The new dataset accounts for the fact that officially pegging to one currency is uninformative about the exchange rate regime prevailing vis-a-vis other currencies, and it allows characterizing bilateral exchange rate regimes based on countries' ex-ante announcements rather than ex-post observations. We present a simple model that suggests that announced exchange rate stability enhances bilateral FDI flows. The empirical evidence we provide offers some support to this claim: countries that are linked by a non-floating exchange rate regime seem to attract significantly more FDI from each other. In particular, relationships with no separate legal tender like currency unions are most favorable to FDI in both developed and developing countries. Moreover, we find substantial differences between developing and developed countries, with the effect of announced exchange rate stability being much stronger for the former group than for the latter.
Keywords: F21; F23; O24; F21; F23; O24; 330; Exchange rate regimes; Foreign direct investment; Gravity equation